Formononetin, a methoxy isoflavone, enhances bone regeneration in a mouse model of cortical bone defect. Issue 11 (10th July 2017) - Singh, Krishna Bhan; Dixit, Manisha; Dev, Kapil; Maurya, Rakesh; Singh, Divya
Abstract: The bone regeneration and healing effect of formononetin was evaluated in a cortical bone defect model that predominantly heals by intramembranous ossification. For this study, female Balb/c mice were ovariectomised (OVx) and a drill-hole injury was generated in the midfemoral bones of all animals. Treatment with formononetin commenced the day after and continued for 21 d. Parathyroid hormone (PTH1–34 ) was used as a reference standard. Animals were killed at days 10 and 21. Femur bones were collected at the injury site for histomorphometry studies using microcomputed tomography ( μ CT) and confocal microscopy. RNA and protein were harvested from the region surrounding the drill-hole injury. For immunohistochemistry, 5 µm sections of decalcified femur bone adjoining the drill-hole site were cut. μ CT analysis showed that formononetin promoted bone healing at days 10 and 21 and the healing effect observed was significantly better than in Ovx mice and equal to PTH treatment in many aspects. Formononetin also significantly enhanced bone regeneration as assessed by calcein-labelling studies. In addition, formononetin enhanced the expression of osteogenic markers at the injury site in a manner similar to PTH. Formononetin treatment also led to predominant runt-related transcription factor 2 and osteocalcin localisation at the injury site. These results support the potential of formononetin to be a bone-healing agent and are suggestive of its promising role in the fracture-repair process.